The effect of cooperative learning in the development of reading skills of students of 7th semester. - Ortega Pillasagua, Saul Omar (2023)
This project is based on analyzing the either positive or negative use of the Cooperative Learning within a problematic that has been evidenced in the students of the 7th semester of the Peninsula State University of Santa Elena belonging to the major of Pedagogy of National and Foreign Languages, in reading skills. In addition, it analyzes which techniques are most used by teachers, based on the aforementioned method. This research is based on a previous survey performed to the same students, who responded to the Cooperative Learning Method as the method of preference for teachers. Also, its methodology is based on the qualitative method using both, one-and-one interviews and focus group techniques data collection, in order to obtain significant and real results. This research resulted in an open-ended conclusion, since results obtained from students were totally opposite with teachers' opinions about the method and techniques applied.